Development of Holokul: 3D Hologram Learning Media on Molecular Structure - Pamenang, Fransisca Ditawati Nur; Nathasya, Paschalia Melinda (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
Learning media refers to equipment designed and developed to convey information, facilitating the effective transmission of knowledge. Molecular structure is a complex chemical concept containing abstract ideas, which can challenge student comprehension. To address this, the development of 3D hologram learning media for molecular structures aims to provide students with a visual representation for enhanced understanding. This research aims to (1) understand the process of developing 3D hologram learning media for molecular structures via the ADDIE development model and (2) assess the validity and practicality of the developed media. The supporting instruments for this research include product and instrument validation sheets, product readability questionnaires, and question items. The study involved six students from the 12th grade. Descriptive analysis of the data reveals that the developed product aligns with the ADDIE model, achieving a validation rate of 90%. The practicality of the product is determined to be 89%. Therefore, the developed product can be utilized as a learning media for molecular structures via 3D holograms.